Investigating the Immunological and Biological Equilibrium of Reservoir Hosts and Pathogenic Leptospira: Balancing the Solution to an Acute Problem? - Putz, Ellie J.; Nally, Jarlath E. (Frontiers in Microbiology, 2020)
Leptospirosis is a devastating zoonotic disease affecting people and animals across the globe. Pathogenic leptospires are excreted in urine of reservoir hosts which directly or indirectly leads to continued disease transmission, via contact with mucous membranes or a breach of the skin barrier of another host. Human fatalities approach 60,000 deaths per annum; though most vertebrates are susceptible to leptospirosis, complex interactions between host species and serovars of Leptospira can yield disease phenotypes that vary from asymptomatic shedding in reservoir hosts, to multi-organ failure in incidental hosts. Clinical symptoms of acute leptospirosis reflect the diverse range of pathogenic species and serovars that cause infection, the level of exposure, and the relationship of the pathogen with the given host. However, in all cases, pathogenic Leptospira are excreted into the environment via urine from reservoir hosts which are uniformly recognized as asymptomatic carriers. Therefore, the reservoir host serves as the cornerstone of persistent disease transmission. Although bacterin vaccines can be used to abate renal carriage and excretion in domestic animal species, there is an urgent need to advance our understanding of immune-mediated host-pathogen interactions that facilitate persistent asymptomatic carriage. This review summarizes understanding of host-pathogen interactions in the reservoir host and prioritizes research to unravel mechanisms that allow for colonization but not destruction of the host. This information is required to understand, and ultimately control, the transmission of pathogenic Leptospira.